Performance Investigation of Single Switch Dual Output DC-DC SEPIC Converter for PV Applications - Dr. N.Rathina Prabha, Dr. J.Gnanavadivel*, Ms. K.S.Krishna Veni (International Journal of Advanced Science and Technology, 2020)
This paper deals with multiplier SEPIC converter with photovoltaic cell as the source. The multiplier SEPIC can achieve high voltage gain with devoid of extreme duty cycle and transformer. It experiences low voltage stress when compared with other buck boost converter. This is very important aspect for renewable energy sources. Further the voltage gain can be extended with the addition of diode and capacitor to the basic SEPIC structure. The basic SEPIC structure is known as 1x level. The converter works with 22V, 100W as input voltage and input power. The operating switching frequency is 20 kHz.  This converter aims for regulating the output voltage to 48V by PI controller for different temperature and irradiation level. The multiplier SEPIC is simulated and the output is validate using MATLAB/SIMULINK.Keywords: Photovoltaic cell, multiplier SEPIC, renewable energy application, PI controller